A Global Data Set of Present‐Day Oceanic Crustal Age and Seafloor Spreading Parameters. (2nd October 2020) - Seton, Maria; Müller, R. Dietmar; Zahirovic, Sabin; Williams, Simon; Wright, Nicky M.; Cannon, John; Whittaker, Joanne M.; Matthews, Kara J.; McGirr, Rebecca
Abstract: We present an updated oceanic crustal age grid and a set of complementary grids including spreading rate, asymmetry, direction, and obliquity. Our data set is based on a selected set of magnetic anomaly identifications and the plate tectonic model of Müller et al. (2019, 10.1029/2018TC005462 ). We find the mean age of oceanic crust is 64.2 Myr, slightly older than previous estimates, mainly due to the inclusion of pockets of Mesozoic aged crust in the Atlantic and Mediterranean and improvements to the Jurassic Pacific triangle. This older crust is partly compensated by additional Cenozoic‐aged back‐arc basin crust not included in previous models. The distribution of spreading modes based on area of preserved crust is relatively equal between slow (20–55 mm/yr) and fast (75–180 mm/yr) spreading systems at 33% and 39%, respectively. Crust transitional between fast and slow, or intermediate systems (55–75 mm/yr), cover 20% of the preserved ocean floor with much smaller proportions of crust formed at ultraslow (5%) and super‐fast (3%) spreading systems. Slow and intermediate spreading systems exhibit the most stable behavior in terms of spreading asymmetry and obliquity, with the widest distribution of obliquities occurring at ultraslow spreading systems, consistent with present‐day observations. Our confidence grid provides a complementary resource for nonexperts to identify those parts of the age grid that are least well constrained. Our grids in 6, 2, and 1 arc min resolution as well as our python workflow, isopolate, used to compute our data sets are freely available in online repositories and on the GPlates data portal. Plain Language Summary: The age of the ocean floor is one of the fundamental data sets for understanding plate tectonic processes. We have generated an updated present‐day age grid of oceanic crust by incorporating recent improvements to the underlying plate motion model, magnetic anomaly identifications, and fracture zones. The resultant mean age of the ocean floor is ~64 million years, slightly older than previous studies. We also present data sets showing various seafloor spreading parameters such as spreading rate, asymmetry, direction, and obliquity. Slow and intermediate seafloor spreading rates produce the most stable spreading behavior in terms of asymmtery and obliquity. Our data sets and workflows are freely available and can be used for multidisciplinary scientific studies. Our maps are an effective visual tool to understand plate tectonic concepts and can be used for education and outreach. Key Points: New oceanic crustal age grid and complementary grids of spreading rate, asymmetry, direction, and obliquity are presented Mean oceanic crustal age of 64.2 million years is reported; slow‐ and fast‐spreading systems are the most common by area All gridded data sets as well as the workflows are made freely available